Bending of light from Reissner-Nordstrom-de Sitter-monopole black hole - SEÇUK, MUHAMMED HALUK; DELİCE, ÖZGÜR (SPRINGER HEIDELBERG, 2020)
We study light deflection from a Reissner-Nordstrom-de Sitter black hole in the gravitational monopole background. We first calculate the orbit equation and the contribution of the monopole and black hole parameters to the deflection angle up to second order for the vanishing cosmological constant case using the Rindler-Ishak method. We also obtain the contribution of the cosmological constant to light deflection in this geometry in the weak field limit using the same method.
Keywords: GRAVITATIONAL DEFLECTION; FIELD